2001
DOI: 10.1063/1.1406981
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of ferroelectric 90°-domain switching in epitaxial Pb(Zr, Ti)O3 thin films by synchrotron x-ray diffraction

Abstract: Switching behavior of 90° domains in epitaxial Pb(Zr0.32Ti0.68)O3 thin films under applied bias voltage was investigated in situ using synchrotron x-ray diffraction, and contribution of the switching to ferroelectric P–E hysteresis curve could be estimated. The electric field in the region illuminated by x ray was made confined exactly normal to the film/substrate interface by patterning an isolated capacitor (1×1 mm2) and etching off the remainder in order to eliminate mechanical constraint from nonswitching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…In ceramics, to induce the 90 o domain reorientation from their equilibrium position high electric fields are necessary due to their high threshold field level, 9, 28 thus inducing a strong internal mechanical stress. 18,28,51 Therefore, mechanically this process may be visualized as being composed by a restoring force (F R ) that forces the domains to come partially back to their equilibrium position. Additionally, it may be assumed that the switching of the domains occurs in a viscous medium.…”
Section: Frequency Dependence Of the Backswitchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In ceramics, to induce the 90 o domain reorientation from their equilibrium position high electric fields are necessary due to their high threshold field level, 9, 28 thus inducing a strong internal mechanical stress. 18,28,51 Therefore, mechanically this process may be visualized as being composed by a restoring force (F R ) that forces the domains to come partially back to their equilibrium position. Additionally, it may be assumed that the switching of the domains occurs in a viscous medium.…”
Section: Frequency Dependence Of the Backswitchingmentioning
confidence: 99%
“…6,7 Nevertheless, due to the high complexity of the polycrystalline structure, the domain reorientation process in bulk ceramics 8,9 and thin films 10,11,12 have been presented much more complex than that observed for the single crystals. It has been interpreted as two successive 90°r otation followed by a 90° domain wall rearrangement instead of a pure 180° flipping.…”
Section: Introductionmentioning
confidence: 99%
“…It is the so-called extrinsic contribution [11]. Several groups showed that PZT bulk and thin films in the tetragonal phase experience a to c domain switching while electric field is applied [12][13][14][15]. In this paper, we show in situ structural modifications in MPB PZT films versus electric field and compare with their piezoelectric properties.…”
mentioning
confidence: 99%
“…These varying experimental results suggest that the mobility of ferroelastic domain walls strongly depends on the specific system and the local environment, that is, the microstructure. This relationship between dynamic domain behaviour and microstructure remains unclear since it is difficult to extract these details from the large area aggregate responses measured with bulk techniques, such as X-ray diffraction or electrical characterization, or with surface probe techniques that provide limited subsurface microstructure information 2,[6][7][8][9][10]15 . Recently developed in situ transmission electron microscopy (TEM) techniques, which enable switching behaviour to be correlated with specific microstructure and defects, provide a unique opportunity for domain dynamics studies 12,[19][20][21][22][23] .…”
mentioning
confidence: 99%
“…For these materials, a long-standing, controversial question persists about the mobility of ferroelastic domain boundaries during ferroelectric switching [1][2][3][4][5][6][7][8][9][10][11][12] . Such boundaries separate regions where both the polarization vector and spontaneous strain change across the boundary.…”
mentioning
confidence: 99%